Quantitative reconstruction of pore-pressure historyin sedimentary basins using fluid escape pipes - Cartwright, J; Kirkham, C; Foschi, M; Hodgson, N; Rodriguez, K; James, D (Geological Society of America, 2021)
We present a novel method to reconstruct the pressure conditions responsible for the formation of fluid escape pipes in sedimentary basins. We analyzed the episodic venting of high-pressure fluids from the crests of a large anticlinal structure that formed off the coast of Lebanon in the past 1.7 m.y. In total, 21 fluid escape pipes formed at intervals of 50–100 k.y. and transected over 3 km of claystone and evaporite sealing units to reach the seabed. From fracture criteria obtained from nearby drilling, we calculated that overpressures in excess of 30 MPa were required for their formation, with pressure recharge of up to 2 MPa occurring after each pipe-forming event, resulting in a sawtooth pressure-time evolution. This pressure-time evolution is most easily explained by tectonic overpressuring due to active folding of the main source aquifer while in a confined geometry.